PENGEMBANGAN E-MODUL MATEMATIKA DENGAN BANTUAN HEYZINE UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - jefri yosua Simorangkir; Rahmatika Elindra; Marzuki Ahmad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to develop a mathematics e-module assisted by Heyzine to enhance students¡¯ mathematical problem-solving abilities at SMP Negeri 1 Batang Toru. It also seeks to evaluate the validity, practicality, and effectiveness of the instructional media using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation).The participants of the study consisted of 29 eighth-grade students (class VIII-2) from SMP Negeri 1 Batang Toru. Data were collected through questionnaire,tests, and documentation. The instruments employed included 1) Validation questionnaires completed by experts to assess product validity and student response questionnaires to determine product practicality; and 2) Test sheets to measure the effectiveness of the developed product. Validation was conducted by media, content, and language experts. Subsequently, a field trial was carried out to assess students’ responses and test results related to mathematical problem-solving skills. The findings indicated that the developed product achieved an average validity score of 88.9%, categorized as